How has the presidential election affected young Americans? - Melissa DeJonckheere; Andre Fisher; Tammy Chang (BMC, 2018)
Abstract The 2016 presidential election season and subsequent political events have had physical and emotional impacts on youth. We collected qualitative insights from 14 to 24 year olds across the US related to these events over time. Open-ended probes were sent via text message at three time points before and after the 2016 presidential election. The majority of youth reported emotional stress during all three time points, and female participants were significantly more likely to experience emotional responses. White participants were more likely to report negative symptoms than their peers both pre-election and at 4-months post-election. While preliminary, the results indicate that feelings of stress, anxiety, and fear have persisted in the months following the election, particularly for young women. Additional research is needed to examine the long-term effects of political events on the emotional and physical health of youth.